THE EFFECTIVENESS OF DONALD E SUPER'S CAREER APPROACH TOWARDS STUDENTS' CAREER DECISION MANAGEMENT AS SEEN IN THE PARENTAL PATTERN AT MAS MUHAMMADIYAH 1 MEDAN - Amelia Afra Kamilah; Gusman Lesmana (Program Studi Bimbingan dan Konseling FKIP UMSU, 2026)
This study is motivated by the relatively low ability of students to effectively manage and make appropriate career decisions, which is often associated with limited self-understanding and inadequate career planning. The present study aims to examine the effectiveness of career guidance services based on the career development theory of Donald E. Super in improving students’ career decision-making management, with consideration of parental parenting patterns as a contextual factor, at MAS Muhammadiyah 1 Medan. A quantitative approach with a pretest–posttest experimental design was employed. The sample consisted of 64 students selected through purposive random sampling. The intervention involved structured career guidance services grounded in Super’s career development approach. Data were collected using a career decision-making management questionnaire and analyzed using descriptive statistics and paired sample t-test. The findings indicate a significant improvement in students’ career decision-making management following the intervention. The hypothesis testing results revealed a significance value of 0.000 (p 0.05), confirming a statistically significant effect of Super’s career development approach on students’ career decision-making management. These findings suggest that the application of Super’s approach is effective in enhancing students’ career decision-making maturity, particularly when aligned with supportive parenting patterns